Three new species of Marcgraviaceae from Costa Rica, with references to related species and notes on the generic placement of Schwartzia jimenezii - Hammel, Barry (2015)
Marcgravia glandulosomarginata, Ruyschia moralesii and Schwartzia tarrazuensis, woody epi- phytes known mostly from mid-elevation rainforest of Costa Rica’s pacific coastal mountains just south of San José, are described, compared to related species and illustrated. The new Marcgravia species is known also from Panama and Colombia, but the other two species are endemic to Costa Rica.